2020
DOI: 10.1108/jfep-10-2019-0207
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country income variations and inclusive financing

Abstract: Purpose This study, a symposium, aims to explore the determinants of financial inclusion, impact of cross-country income-variations on financial inclusion, do high-income countries really uplift the financial inclusion and does the higher financial inclusion index indicate the larger economy? Design/methodology/approach This study adopts the panel data model to investigate the impact of high-income countries and low- and middle-income countries on financial inclusion. However, this study further adopts the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…From the seminal paper of Beck and De La Torre (2007) to the studies by Demirgüç-Kunt et al (2022) and Kumar (2013), research has found that financial inclusion entails access to and intensive use of financial services on a large scale by populations and businesses, regardless of their place of residence, at a low cost. Furthermore, while Sinclair (2001) and Safdar et al (2020) defined financial inclusion as access to mainstream financial services, for Sarma (2008), it is a set of arrangements that facilitate access to, availability of and use of financial services. It is in this vein that Amidžic et al (2014) and Sharma (2016) defined financial inclusion as an economic state in which individuals and firms are not denied access to basic financial services.…”
Section: Introductionmentioning
confidence: 99%
“…From the seminal paper of Beck and De La Torre (2007) to the studies by Demirgüç-Kunt et al (2022) and Kumar (2013), research has found that financial inclusion entails access to and intensive use of financial services on a large scale by populations and businesses, regardless of their place of residence, at a low cost. Furthermore, while Sinclair (2001) and Safdar et al (2020) defined financial inclusion as access to mainstream financial services, for Sarma (2008), it is a set of arrangements that facilitate access to, availability of and use of financial services. It is in this vein that Amidžic et al (2014) and Sharma (2016) defined financial inclusion as an economic state in which individuals and firms are not denied access to basic financial services.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies used first-generation econometric techniques to panel data. These studies ignored the dynamic nature, heterogeneity and cross-section dependency (Sharma, 2016; Sethi and Sethy, 2019; Kim et al , 2018; Safdar et al , 2020; Nandi et al , 2022). In addition, existing studies mostly used individual indicators of financial inclusion (Dar and Ahmed, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another group of publications are articles related to determinants influencing changes in the structure of financial savings in households. The level of financial assets of households in different income groups are considered by among others Safdar, Lin, and Amin (2020) and Honohan (2006). The authors showed that differences in the structure of financial asset allocation depend on age, education and wealth.…”
Section: Introductionmentioning
confidence: 99%